Design and application of support capability evaluation system for complex system. (October 2020) - Wu, Fei; Meng, Zhe; Mao, Hanyuan; Guan, Xujun; Sun, Shaohua
Abstract: Aiming at the problem of low accuracy and effectiveness of complex system support capability assessment, an index system was constructed on the basis of studying the characteristics of support capability generation elements, in which the systematicness, comprehensiveness and the importance of key links of complex system support were considered, a complex system supportability evaluation model was proposed based on weight scores and key levels, and the score and level of the complex system supportability evaluation were obtained through comprehensive evaluation. A corresponding evaluation system was designed which provided the means and support for the informatization of support capability evaluation of complex systems.